FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Ulifah Nurfidha; Muhammad Tahwin (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2021)
The Research is carried out to prove the influences of working capital, liquidity, activity ratio, the level of the companies and the sales’ growth toward the profitability in food and beverage companies registered in Indonesia Stock Exchange. The population of the research is all the food and beverage companies registered in Indonesian Stock Exchange. The sampling technique used is purposive sampling. Data analyzing technique used is multiple linier regression analysis. The research result proves that the working capital gives negative influence not significant toward the profitability. Liquidity, ratio of activities, sales’ growth has positive influence toward profitability. While the independent variable ability of the regression model explains that dependent variable is 68,8%, while 31,2 % is explained by other variable that is not observed in this research.